Studi Literatur Uji Aktivitas Ekstrak Daun Kirinyuh (Chromolaena odorata) Sebagai Alternatif Pengobatan Myiasis yang Disebabkan oleh Chrysomya bezziana - Diana Rabeka Otu; Nemay A Ndaong; Meity M Laut (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Myiasis is a disease in livestock caused by the larvae of the fly Chrysomya bezziana . Myiasis causes economic losses due to decreased productivity and tissue damage in livestock. Treatment of myiasis is by using synthetic insecticides, but the use of synthetic insecticides has a negative impact on animals, humans, and the environment. The use of synthetic insecticides can be replaced with botanical insecticides, one of the plants that can be used as antimyiasis is kirinyuh . Kirinyuh is a plant from the Asteraceae family which has been used as a botanical insecticide. This literature study aims to determine the potential of kirinyuh leaves as antimyiasis, the compounds contained in kirinyuh leaves and the mechanism of antimyiasis. This literature study uses 30 literature collected by browsing the Google Scholar database. Five literature states that kirinyuh leaves contain secondary metabolites of flavonoids, alkaloids, saponins, tannins and terpenoids. Meanwhile, 12 literatures describe the antimyiasis activity of these secondary metabolites. Flavonoids inhibit the nervous system and interfere with energy metabolism in the insect body, alkaloids interfere with the nervous system and reduce insect appetite, saponins as antifeedants and insect growth inhibitors, tannins interfere with insect digestion and growth, and terpenoids as inhibitors of nerve transmission in insects.